Analysis of lactase in lactose intolerance supplements. Issue 6 (21st November 2018) - Stourman, Nina; Moore, Jennifer
Abstract: Lactase is the enzyme responsible for the digestion of the disaccharide lactose, and deficiency in this enzyme causes the prevalent medical condition lactose intolerance. Management of lactose intolerance can be achieved through the administration of lactase supplements. Lactase is an appropriate platform for advanced enzymatic study because its medical application is a motivator for student learning. The following is an upper‐level biochemistry laboratory sequence that integrates student inquiry and exposure to advanced laboratory techniques. Students investigate three different lactase supplements through experimentation that includes the Bradford assay, SDS‐PAGE, continuous and discontinuous kinetic assays, and zymography. Upon completion of this project, students compile their results and conclusions in a scientifically formatted paper comparing supplement protein content and activity. This safe and inexpensive laboratory project enriches student understanding of key biochemical concepts while mirroring work performed in a realistic research setting. © 2018 International Union of Biochemistry and Molecular Biology, 46(6):652–662, 2018.